Análise da relação entre as práticas de gestão do conhecimento e o desempenho operacional de uma organização - Woicik, Alice Maurer Mendes (2022)
The general objective of this research is to analyze the relationship between knowledge management practices and the operational performance of an organization in the automotive sector. The contribution to the knowledge management area is significant in view of the growing importance of people development for the organization performance. The results of this work can be applied to companies in different sectors, particularly those where there is a high dependence on manpower, such as those in the manufacturing and service sectors. The scientific method proposed for this research was the inductive and the research method was the case study based on an automotive industry installed in the Metropolitan Region of Curitiba. Regarding the results, the analysis of the correlation between the performance of the main indicators and knowledge management practices adopted by the organization in the period between 2012 and 2021 showed that not all indicators had their performance influenced by knowledge management practices. It was possible to observe that knowledge management practices had a positive impact on improving the operational performance of the indicators number of improvements and productivity, which may be correlated, contributing reciprocally. Regarding the other indicators analyzed, it was observed that knowledge management practices may have contributed to the maintenance of good results already achieved, but without generating major impacts or influence. Finally, it was concluded that knowledge management practices can be an important resource to be explored by organizations with great operational demand, as a way to promote the improvement of their operational performance, with growth for people and for companies, in benefit of the whole society.